Management Innovativeness and Growth of Occupational Pension Schemes in Kenya - Mitei, Christopher; Omwenga, Jane; Ndururi, Joseph; Ngatia, Peter (International Journal of Entrepreneurship and Project Management, 2025)
Purpose: Management innovation is critical for developing and sustaining occupational pension schemes. AI, blockchain, and machine learning present possibilities to improve efficiency and financial resilience and to strengthen members' confidence. However, essential factors must be met fully for these innovations to thrive, including resistance to change, legal requirements, and technological factors. This review raises awareness of the need to nurture an innovative culture in pension fund management backed up by open policies and directed research. In that respect, adopting innovation will continue to be critical in dealing with these emergent issues and supporting the future viability of various communities worldwide. This study aimed to establish the influence of management innovativeness on the growth of occupational pension schemes in Nairobi City County, Kenya. Methodology: This study used the Schumpeterian Innovation Theory. This study employed a hybrid research design that combined quantitative and qualitative methods. A longitudinal descriptive survey was used in this study. All 809 Nairobi City County occupational pension systems were targeted. In Nairobi City County, Kenya, this study sampled all the Kenya Retirement Benefits Authority occupational programs. 321 projects have fund values under 500 million Kenyan shillings, 275 between 500 million and 1 billion, 158 between 1 billion and 10 billion, and 55 over 10 billion. A biased stratified sampling procedure selected 267 of Nairobi City County's 809 pension schemes. One manager, preferably the Finance and Investments Manager, from each of Nairobi's 267. Findings: The study concluded that management innovativeness significantly influences entrepreneurial culture and the growth of occupational pension schemes in Nairobi. Therefore, management innovativeness is a key determinant in supporting the growth of Occupational Pension Schemes in Kenya. Unique Contribution to Theory, Practice and Policy: Based on the findings of this study, it is apparent that pension schemes need to adopt innovativeness in their business environment. The recommendation from the above study further reveals that only innovative pension schemes will be relevant in the market.